2021
DOI: 10.1002/fsn3.2310
|View full text |Cite
|
Sign up to set email alerts
|

Predicational ability of phase angle on protein energy wasting in kidney disease patients with renal replacement therapy: A cross‐sectional study

Abstract: Objective To investigate the ability of phase angle (PA) and body composition for predicting protein energy wasting (PEW) in renal replacement therapy (RRT) patients. Methods Renal replacement therapy (RRT) patients were enrolled in this study. Body composition was measured by direct segmental multi‐frequency biolectrical impedance analysis method (DSM‐BIA); phase angle (PA), fat‐free mass (FFM), fat mass (FM), mid‐arm circumference (MAC), WC (waist circumference), and ECW/TBW (extracellular water/total body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
1
10
1
1
Order By: Relevance
“…In this study, PhA was found to be an independent predictor of PEW in HD patients (adjOR: 0.308, p = 0.001). As expected, patients with PEW had a lower PhA compared to their non-PEW counterparts [11,15].…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…In this study, PhA was found to be an independent predictor of PEW in HD patients (adjOR: 0.308, p = 0.001). As expected, patients with PEW had a lower PhA compared to their non-PEW counterparts [11,15].…”
Section: Discussionsupporting
confidence: 71%
“…This relationship could be attenuated owing to regression dilution bias because of day-to-day variation in dietary intake [55,56]. However, this did not confiscate the discriminative ability of PhA to detect PEW among HD patients in both current and previous studies [12,15].…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations